2012
DOI: 10.1111/j.1742-481x.2012.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of a new compression system in patients with lymphoedema

Abstract: In the acute phase of lymphoedema, patients require comprehensive decongestive therapy (CDT), which includes skin care, an exercise regimen, manual lymphatic drainage (MLD) and regular bandaging. This study was established to determine the effectiveness of a new system of bandage therapy, the 3M™ Coban™ 2 compression system. In total, 24 patients were entered into the study (12 from UK and 12 from Canada) with a variety of clinical presentations. The mean age of the groups was 57·4 years, which varied from 26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
0
14
0
2
Order By: Relevance
“…The volume of individual segments was calculated using the following formula: where H is the distance between the individual measuring points, ie, the height of the segment, Ct is the circumference at the top of the segment, and Cb is the circumference at the bottom of the segment. 14 The volume of the entire measured limb was calculated by adding the volumes of all the segments. 14 16 Circumferences were given in cm, and volumes in cm 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume of individual segments was calculated using the following formula: where H is the distance between the individual measuring points, ie, the height of the segment, Ct is the circumference at the top of the segment, and Cb is the circumference at the bottom of the segment. 14 The volume of the entire measured limb was calculated by adding the volumes of all the segments. 14 16 Circumferences were given in cm, and volumes in cm 3 .…”
Section: Methodsmentioning
confidence: 99%
“… 14 The volume of the entire measured limb was calculated by adding the volumes of all the segments. 14 16 Circumferences were given in cm, and volumes in cm 3 . BMI, average and maximum limb circumference, and limb volume were analyzed before and after (last day) the treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown good edema reduction in both arms and legs and improvements in symptoms associated with lymphedema. [45,46] lymphedema exercises Physical activity and exercises enhance physical and emotional well-being, increase fitness and vitality and improve health-related QoL outcomes. They are considered another major component of CDT.…”
Section: Manual Lymphatic Drainagementioning
confidence: 99%
“…Die Entstauungsphase sollte, wenn möglich, ambulant durchgeführt werden (25). Bewährt haben sich dafür Mehrkomponenten-Kompressionssysteme aus Unterpolsterung und adhäsiven Kurzzugbinden (7,16,17). Diese Kompressionsbandagierungen sollten in Analogie zur komplexen physikalischen Entstauung (KPE) in der Lymphödemtherapie über je 24 h getragen werden und mit einer rückfettenden Hautpflege, Bewegung in der Kompression und manueller Lymphdrainage kombiniert werden (5).…”
Section: Diagnostik and Therapie Konzeptunclassified